2010
DOI: 10.1182/blood-2009-08-236760
|View full text |Cite
|
Sign up to set email alerts
|

Defective ubiquitin-mediated degradation of antiapoptotic Bfl-1 predisposes to lymphoma

Abstract: The antiapoptotic Bcl-2 family member Bfl-1 is up-regulated in many human tumors in which nuclear factor-kappaB (NF-kappaB) is implicated and contributes significantly to tumor cell survival and chemoresistance. We previously found that NF-kappaB induces transcription of bfl-1 and that the Bfl-1 protein is also regulated by ubiquitin-mediated proteasomal degradation. However, the role that dysregulation of Bfl-1 turnover plays in cancer is not known. Here we show that ubiquitination-resistant mutants of Bfl-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…In contrast, Bcl-2, Bcl-w, and Bcl-xL were stable, with half-lives of about 20 hours. This agrees with published data on the untagged proteins, 14,22,36,37 indicating that GFP fusion did not influence the turnover of the Bcl-2 proteins. Accordingly, the turnover of GFP-Bcl-2 and GFP-Mcl-1 was virtually identical to that of endogenous Bcl-2 and Mcl-1 in the same cells (supplemental Figure 7).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, Bcl-2, Bcl-w, and Bcl-xL were stable, with half-lives of about 20 hours. This agrees with published data on the untagged proteins, 14,22,36,37 indicating that GFP fusion did not influence the turnover of the Bcl-2 proteins. Accordingly, the turnover of GFP-Bcl-2 and GFP-Mcl-1 was virtually identical to that of endogenous Bcl-2 and Mcl-1 in the same cells (supplemental Figure 7).…”
Section: Resultssupporting
confidence: 92%
“…6,13,19 These results do not fully agree (Figure 2 line 1) and do not necessarily reflect binding in cells, particularly because the mitochondrial membrane context is lacking. 20,21 Also, removal of the membrane anchor from the prosurvival Bcl-2 proteins can alter binding properties, [22][23][24] and BH3-peptides may not represent the full-length proteins. 25,26 Most likely for these reasons, BH3-binding profiles of Bak and Bax determined in vitro differ greatly from those determined by coimmunoprecipitation from cells 27 ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Yang et al (2005) added green fluorescent protein (GFP) to Bfl-1 to discover the intracellular localisation and instead found that fusion with GFP at either the C-or N-terminus converted Bfl-1 into a potent pro-apoptotic protein and induced cell death 426 . However this discovery has not been confirmed by other research groups such as Fan et al 427 and Simmons et al 371 , who have used GFP to tag Bfl-1, as commercial antibodies which recognise the protein have only become available in recent years.…”
Section: The Localisation Of Bfl-1mentioning
confidence: 94%
“…Ubiquitin-resistant and hence more stable mutants of BCL2A1 have been described to promote lymphoma, highlighting the importance of post-translational regulation of BCL2A1 in a physiological context. 86 Although not tumorigenic by itself in mice, 63 enforced expression of BCL2A1 was found to accelerate myc-induced leukemogenesis upon engraftment in mice. However, when compared with other anti-apoptotic BCL2 proteins, the effect of BCL2A1 overexpression on the survival of leukemic mice was less pronounced.…”
Section: A Function Of Bcl2a1 In Tumorigenesismentioning
confidence: 97%